Arv1 promotes cell division by recruiting IQGAP1 and myosin to the cleavage furrow. Issue 5 (3rd March 2016) - Sundvold, Hilde; Sundvold-Gjerstad, Vibeke; Malerød-Fjeld, Helle; Haglund, Kaisa; Stenmark, Harald; Malerød, Lene
ABSTRACT: Cell division is strictly regulated by a diversity of proteins and lipids to ensure proper duplication and segregation of genetic material and organelles. Here we report a novel role of the putative lipid transporter ACAT-related protein required for viability 1 (Arv1) during telophase. We observed that the subcellular localization of Arv1 changes according to cell cycle progression and that Arv1 is recruited to the cleavage furrow in early telophase by epithelial protein lost in neoplasm (EPLIN). At the cleavage furrow Arv1 recruits myosin heavy chain 9 (MYH9) and myosin light chain 9 (MYL9) by interacting with IQ-motif-containing GTPase-activating protein (IQGAP1). Consequently the lack of Arv1 delayed telophase-progression, and a strongly increased incidence of furrow regression and formation of multinuclear cells was observed both in human cells in culture and in follicle epithelial cells of egg chambers of Drosophila melanogaster in vivo . Interestingly, the cholesterol-status at the cleavage furrow did not affect the recruitment of either IQGAP1, MYH9 or MYL. These results identify a novel function for Arv1 in regulation of cell division through promotion of the contractile actomyosin ring, which is independent of its lipid transporter activity.